Changes in clinical practice perceptions and mental health of sports medicine physicians due to the SARS-CoV-2 pandemic. Issue 5 (3rd September 2022) - Cushman, Daniel M.; York, Elizabeth; Asay, Alexandra; Ross, Brendon; Teramoto, Masaru; McCormick, Zachary L.
ABSTRACT: Objective: The SARS-CoV-2 pandemic has had an immense impact on healthcare, but little has been published on its impact on sports medicine physicians. This study aimed to assess the perceived impacts of the pandemic on practice changes, financial implications, and mental health of the physician members of the American Medical Society for Sports Medicine (AMSSM). Methods: Online surveys were sent to physician members of the AMSSM, with questions asking about demographic information and personal associations to COVID-19. The main outcome measures included self-reported clinical practice volumes, visit types (telemedicine, face-to-face), Patient Health Questionnaire (PHQ-4) scores, personal finances, clarity of practice guidelines, and personal protective equipment (PPE) availability. Results: A total of 825 respondents completed the initial survey, with a subset completing follow-ups. In-person clinical and procedural volumes were reported to be reduced to just 17.9% and 13.7% of the pre-pandemic baseline volumes at the first survey (March 2020), but increased to 81.1% and 77.3% (August 2020), respectively. PHQ-4 anxiety subscores significantly decreased over time ( p < 0.001); younger physicians and female physicians were more likely to have higher scores ( p < 0.05). Reported physician income significantly increased over time ( p < 0.05), and financial concerns steadily decreased ( p < 0.001). The perception of having an adequate PPE significantly increased over the study ( p < 0.001) but not for having clear practice guidelines ( p > 0.05). Physicians have become increasingly aware of others testing positive for the virus, but not themselves or someone they live with. Conclusions: Sports medicine physicians have been heavily impacted by the SARS-CoV-2 pandemic, with some recovery since it started. Sports medicine physicians should be aware of pandemic-related practice changes and resulting mental health and financial implications.